Classification of esophageal motor findings in gastro‐esophageal reflux disease: Conclusions from an international consensus group. Issue 12 (24th May 2017) - Gyawali, C. P.; Roman, S.; Bredenoord, A. J.; Fox, M.; Keller, J.; Pandolfino, J. E.; Sifrim, D.; Tatum, R.; Yadlapati, R.; Savarino, E.
Abstract: Background: High‐resolution manometry (HRM) has resulted in new revelations regarding the pathophysiology of gastro‐esophageal reflux disease (GERD). The impact of new HRM motor paradigms on reflux burden needs further definition, leading to a modern approach to motor testing in GERD. Methods: Focused literature searches were conducted, evaluating pathophysiology of GERD with emphasis on HRM. The results were discussed with an international group of experts to develop a consensus on the role of HRM in GERD. A proposed classification system for esophageal motor abnormalities associated with GERD was generated. Key Results: Physiologic gastro‐esophageal reflux is inherent in all humans, resulting from transient lower esophageal sphincter (LES) relaxations that allow venting of gastric air in the form of a belch. In pathological gastro‐esophageal reflux, transient LES relaxations are accompanied by reflux of gastric contents. Structural disruption of the esophagogastric junction (EGJ) barrier, and incomplete clearance of the refluxate can contribute to abnormally high esophageal reflux burden that defines GERD. Esophageal HRM localizes the LES for pH and pH‐impedance probe placement, and assesses esophageal body peristaltic performance prior to invasive antireflux therapies and antireflux surgery. Furthermore, HRM can assess EGJ and esophageal body mechanisms contributing to reflux, and exclude conditions that mimic GERD. Conclusions & Inferences: Structural and motor EGJ and esophageal processes contribute to the pathophysiology of GERD. A classification scheme is proposed incorporating EGJ and esophageal motor findings, and contraction reserve on provocative tests during HRM. Abstract : Existing high‐resolution manometry metrics describe esophagogastric junction morphology and esophageal body peristaltic patterns. Characterization of esophagogastric junction (EGJ) and esophageal body motor findings in gastro‐esophageal reflux disease (GERD). When the EGJ is abnormal, it can be hypotensive, morphologically abnormal, or both. When esophageal body motor function is abnormal, fragmented peristalsis, ineffective esophageal motility (IEM), and absent contractility are possible. Esophagogastric junction and esophageal body motor function can be both abnormal.